PENGGUNAAN BUKU PAKET UNTUK MEMPERMUDAH PROSES PEMBELAJARAN SISWA DI SMP NEGERI 2 KAMPAR - Rohani Rohani; Nurmalia Nurmalia; Pirma Juragan Rezky Sihombing; Armiati Armiati; Srikartikowati Srikartikowati (JURNAL MANAJEMEN PENDIDIKAN, 2022)
The textbook is a student learning resource with several uses that can simplify the learning process. With textbooks, students can learn more actively in class, students can also repeat lessons from books when they are brought home. Likewise, the teacher can expand the subject matter based on the information contained in it. This paper aims to find ideas on how to use textbooks to facilitate the learning process. To achieve the objective of the observation, the data were obtained using participatory techniques, in-depth interviews, documentation and Focus Group Discussions. Furthermore, the data obtained were analyzed descriptively, namely by providing an explanation of the findings obtained. The research yielded information on the use of textbooks as learning resources for students, textbooks as learning media and increasing students' learning motivation. At SMP Negeri 2 Kampar the use of textbooks was not optimal due to the lack of quotas for textbooks at school, and the lack of quality textbooks given to students. students like there are scribbles and tears.